Utilization of Household Farming with Verticulture Vegetable Cultivation Techniques for the Implementation of a Vegetable Village in Payak Tengah Hamlet, Piyungan, Bantul Regency - Nadia, Nadia; Della Nanda Luthfiana; Andy Ilham H; Hernanda Nur R; Mutia Febriani S.P; Igo Kristian; Agung Pandia; Rike Nur S.G; Dian Nur P; Nur Afif F; Wisnu Hariadi; Fadil Rozaqi; Revan Suwito (PT FORMOSA CENDEKIA GLOBAL, 2023)
This empowerment aims to optimize the function of residents' home yards by using horticulture vegetable cultivation techniques to produce a vegetable village. To achieve this, an initial understanding of the importance of home farming, which will enable residents to use yard land, is needed. In this Real Work Lecture-Thematic or KKN-T, the implementation method is carried out through education and socialization to residents to maximize empowerment results. articipating in activities, showing the enthusiasm of residents utilizing yard land, and the existence of a vegetable cultivation pilot project using home yards to grow vegetables with viticulture techniques for vegetable village cultivation can be achieved.